Serum apoptosis markers related to liver damage in chronic hepatitis C: sFas as a marker of advanced fibrosis in children and adults while M30 of severe steatosis only in children - Valva, Pamela (2013)
Background: Liver biopsy represents the gold standard for evaluating damage and progression in patients with chronic hepatitis C (CHC); however, developing noninvasive tests that can predict liver injury represents a growing medical need. Considering that hepatocyte apoptosis plays a role in CHC pathogenesis; the aim of our study was to evaluate the presence of different apoptosis markers that correlate with liver injury in a cohort of pediatric and adult patients with CHC. Methods: Liver biopsies and concomitant serum samples from 22 pediatric and 22 adult patients with CHC were analyzed. Histological parameters were evaluated. In serum samples soluble Fas (sFas), caspase activity and caspase-generated neoepitope of the CK-18 proteolytic fragment (M30) were measured. Results: sFas was associated with fibrosis severity in pediatric (significant fibrosis p=0.03, advanced fibrosis p=0.01) and adult patients (advanced fibrosis p=0.02). M30 levels were elevated in pediatric patients with severe steatosis (p=0.01) while in adults no relation with any histological variable was observed. Caspase activity levels were higher in pediatric samples with significant fibrosis (p=0.03) and they were associated with hepatitis severity (p=0.04) in adult patients. The diagnostic accuracy evaluation demonstrated only a good performance for sFas to evaluate advanced fibrosis both in children (AUROC: 0.812) and adults (AUROC: 0.800) as well as for M30 to determine steatosis severity in children (AUROC: 0.833). Conclusions: Serum sFas could be considered a possible marker of advanced fibrosis both in pediatric and adult patient with CHC as well as M30 might be a good predictor of steatosis severity in children.